Cultura organizacional: um estudo de caso detectando os elementos que favorecem a mudança da organização - Chesini, Cláudia (2004)
In changing times, when there is a frenzy in search of more quality, optimization, speed, reengineering, esthetic, happiness the human being, in its way of living and having relationships in society, organizes itself in a way of providing its necessities. As these necessities change, the way of organizing also changes and consequently the various aspects that make up the society. The organizational changing comes from the dynamic of the organization and the society, having present that the organization is built up as an instrument to the reach of the society s welfare, and thus developing the adaptations necessaries. The present dissertation analysed, in an empiric way, the changing process developed in an institution of private teaching in the West Border of RS, in the last twenty years, comprising the period from 1981 to 2002. The survey was developed in a way of a simple case study, of qualitative nature, viewing to understand the phenomena of changes in the organization. The data collection was done through semi-structured interviews with emphasis in the aspects that characterize the development of the changing process, such as the general conditions, the leadership, the cultural factors, the restrictions and limitations Besides these informations sources, documents of the organization were used. In this analysis was done the proposal reading by Alves (1997), Pettigrew (1991), Freitas (1994), Blake & Mouton (1964), among others authors. Then were identified lie elements of changing in the organization the external factors as governmental laws, economic plans, organs of class (AEC, SINEPE ) and internal factors like communication, information technology, involvement in the process. Stand out the leaders hip between culture and change organizational where being aware of the culture of organization, with a personal style, realize actions that the change.